Perceived language proficiency and pain assessment by registered and student nurses in native English‐speaking and EAL children aged 4–7 years. Issue 5 (10th January 2018) - Azize, Pary M; Cattani, Allegra; Endacott, Ruth
Abstract : Aims and objectives: To identify the factors that influence decisions made by health professionals when assessing the pain of native English speaking and children whose English is an additional language. Background: Pain assessment in children is often poorly executed following acute injury. Whilst a range of pain assessment tools have been developed, little guidance is provided for assessing pain in children with English as an additional language. Design: Factorial survey design. Methods: Twenty minor injuries unit nurses and 20 children's nursing students participated in an electronic survey to make judgements on 12 scenarios describing a child attending a minor injuries unit following an incident, accompanied by a parent. Respondents had to decide the most important form of pain assessment, and whether they would ask a parent or an interpreter to assess the pain of the child. An open‐ended question asked about the difficulties found in making a judgement. Results: Observation of the child's behaviour was the most common pain assessment reported. The visual analogue scale was significantly associated with children with proficient English. Respondents were significantly more likely to involve parents in the assessment if they could speak English well compared to parents with poor English skills. Moreover, nursing students were significantly more likely than registered nurses to call for support from an interpreter. Thematic analysis identified three themes related to difficulties with pain assessment: contrasting approaches, differing perceptions of pain and overcoming challenges. Conclusions: The reduced ability to communicate between child, parent and healthcare professional highlights the need to identify forms of assessment based on individual cases. Relevance to clinical practice: The number of children with English as an additional language has seen a marked rise over the last decade. In situations where communication ability is reduced, assessment of pain should be tailored to meet the needs of the child. This may require timely access to interpreter services.